The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1074/jbc.m611043200
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Role of the Cyclin-dependent Kinase Inhibitor p21WAF1/CIP1 in Apoptosis and Autophagy

Abstract: Programmed cell death (PCD) is involved in a variety of biologic events. Based on the morphologic appearance of the cells, there are two types of PCD as follows: apoptotic (type I) and autophagic (type II). However, the molecular machinery that determines the type of PCD is poorly defined. The purpose of this study was to show whether the presence of the cyclin-dependent kinase (CDK) inhibitor p21, a modulator of apoptosis, determines which type of PCD the cell undergoes. Treatment with C 2 -ceramide was assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 53 publications
2
79
0
Order By: Relevance
“…2 and 4). As p53 downstream target p21 functions as a suppressor of apoptosis and autophagy (17,18), p21 suppression may be a critical factor to induce dual programmed cell death pathways in response p53 overexpression. Suppression of p21 expression by genetic deletion or artificial p21 target microRNA has been shown to enhance the Ad-p53-induced apoptosis (18,35).…”
Section: Mol Cancer Ther; 12(3) March 2013mentioning
confidence: 99%
See 1 more Smart Citation
“…2 and 4). As p53 downstream target p21 functions as a suppressor of apoptosis and autophagy (17,18), p21 suppression may be a critical factor to induce dual programmed cell death pathways in response p53 overexpression. Suppression of p21 expression by genetic deletion or artificial p21 target microRNA has been shown to enhance the Ad-p53-induced apoptosis (18,35).…”
Section: Mol Cancer Ther; 12(3) March 2013mentioning
confidence: 99%
“…Dual cell death pathways, such as apoptosis and autophagy, induced by p53 transactivation are mainly involved in the suppression of tumor initiation and progression. However, among the p53 downstream target genes, p21, which is most rapidly and strongly induced during the DNA damage response, mainly induces cell-cycle arrest through suppression of apoptotic and autophagic cell death pathways (17,18). Thus, p21 suppression may be a more effective strategy for the induction of apoptotic and autophagic cell death pathways in tumor cells, particularly when the tumor suppressor p53 gene is overexpressed in tumor cells in response to cancer gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…As opposed to p27, the role of another CDK inhibitor p21 is more equivocal. Although p21 has been shown to impair C(2)-ceramide-and CD40-induced autophagic activity, enforced expression of cytoplasmic p21 induces autophagy (Fujiwara et al, 2008;Portillo et al, 2010;. These findings indicate that, similar to p53, the regulatory effect of p21 on autophagy may depend on its subcellular localization.…”
Section: V12mentioning
confidence: 93%
“…30 A recent study indicates that p21 acts as a mediator of the apoptotic pathway and a negative regulator of autophagy. 31 We previously showed that statins increased p21 expression through inhibition of HDAC activity. 32 Furthermore, statins were found to induce p21-dependent autophagy.…”
Section: Hdac Inhibitors Induced Autophagymentioning
confidence: 97%